Attitudes of pharmacy and nutrition students towards team-based care after first exposure to interprofessional education in Qatar. Issue 1 (January 2015) - Wilby, Kyle John; Al-Abdi, Tamara; Hassan, Abdelmonem; Brown, Marian Amanda; Paravattil, Bridget; Khalifa, Sherief Ibrahim
Abstract Little is known regarding attitudes of healthcare professional students towards team-based care in the Middle East. As modernization of health systems is rapidly occurring across the Gulf Cooperation Council countries, it is important for students to engage in interprofessional education (IPE) activities. The objective of this study was to assess pre-clinical students' attitudes towards interprofessional healthcare teams after completion of their first IPE activity. A previously validated questionnaire was distributed to 25 pharmacy and 17 nutrition students at Qatar University after participation in an IPE event. Questions related to quality of team-based care and physician centricity. Results showed high agreement regarding high quality care provided by teams yet students were unsure of the value of team-based care when considering required time for implementation. Results provide baseline data for future studies to assess student attitudes throughout the professional programs and give valuable insight for future IPE program design in the Middle East.